A survey of academic libraries in cities of Region V with implications for resource sharing - Pasamba, Nehemias A. (1987)
This descriptive research aims to survey the existing facilities and services of the academic libraries in cities of Naga,Legaspi and Iriga as prospects for possible library resource sharing and cooperation in the region.